2014
DOI: 10.1097/mpa.0000000000000084
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas Transplantation From Donors After Cardiac Death

Abstract: Pancreata procured by DCD have comparable outcomes to those procured after brain death. Donation after cardiac death pancreas transplant is a viable method of increasing the donor pool, decreasing wait list mortality, and improving the quality of life for type 1 diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…Deceased donor type was not a risk factor for pancreas damage, unlike kidney or liver procurement where DCD donors appear to have higher rates of injuries (10,13). This finding is difficult to explain, but it is reassuring given the high proportion of DCD pancreas donors in the UK and their acceptable short-term outcomes (4,19).…”
Section: Discussionmentioning
confidence: 80%
“…Deceased donor type was not a risk factor for pancreas damage, unlike kidney or liver procurement where DCD donors appear to have higher rates of injuries (10,13). This finding is difficult to explain, but it is reassuring given the high proportion of DCD pancreas donors in the UK and their acceptable short-term outcomes (4,19).…”
Section: Discussionmentioning
confidence: 80%
“…Two studies reported survival but not in a way we could use the data, so we were unable to include these in the overall analysis. 8,29 Overall, results indicated there was no significant difference in allograft survival between DCD and DBD pancreases (HR, 0.98; 95% CI, 0.74-1.31; P = 0.92) (see Figure 2). There was no evidence of heterogeneity among these studies (P = 0.47).…”
Section: Survivalmentioning
confidence: 78%
“…6 Although recent studies report that DCD kidney transplants have similar outcomes to donor after brain death (DBD) kidney transplants, liver transplants from DCD organs are associated with more complications and reduced survival. 7 Promisingly, some large studies comparing pancreas transplants from DCD and DBD donors demonstrated similar patient survival and allograft survival across these groups 8 and similar rates of allograft survival at 10 years. 9 Guidelines for DCD donor organ retrieval from the American Society of Transplant Surgeons suggest that optimal withdrawal of ventilatory and organ perfusion support will occur in the operating room where heparin administration and antemortem cannulation may be used.…”
mentioning
confidence: 97%
“…Despite these benefits, there has been a 30% decline in the number of pancreas transplants performed in United States since reaching a peak in 2004, when 1484 pancreas transplants were performed . Fewer transplant referrals, improvement in patient‐centered diabetes management, a proportional rise in donor after cardiac death (DCD) donation, and increased discard rates may all be factors in declining pancreas transplant activity …”
Section: Introductionmentioning
confidence: 99%